Penerapan Model Pembelajaran Kooperatif Tipe Group Investigation Menggunakan Media Suling - Cahayu, Kristiana; Hariyani, Sri; Dinulloh, Riski Nur Istiqomah (JRPM (Jurnal Review Pembelajaran Matematika), 2020)
This study aims to describe the steps of Group Investigation learning using suling media that can improve the learning outcomes of students. Group Investigation learning has six steps have identifying topics and organizing into groups, planning the investigation, carrying out the investigating, preparing the final report, presenting the final result, and evaluating. The research is a qualitative approach. The data collection techniques used are tests, observations, interviews, and documentation. Analysis of data used: data reduction, data presentation, and withdrawal of conclusions. The validity of data is the perseverance of observer, triangulation, and peer inspection. This research can improve student learning outcomes. This result shows the percentage of student learning outcomes in the pra cycle amounting to 48% that has a rate of 75 and increased during the first cycle with 80%. The result of teacher observation is 89.28%, while the students’ is 78.57%. Based on the results of interviews conducted on four students who were the subject of interviews, one of which didn’t increase learning outcome, but liked suling media when interviewed.